2017
DOI: 10.1038/s41598-017-07848-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting primary acute myeloid leukemia with a new CXCR4 antagonist IgG1 antibody (PF-06747143)

Abstract: The chemokine receptor CXCR4 mediates cell anchorage in the bone marrow (BM) microenvironment and is overexpressed in 25–30% of patients with acute myeloid leukemia (AML). Here we have shown that a new CXCR4 receptor antagonist IgG1 antibody (PF-06747143) binds strongly to AML cell lines and to AML primary cells inhibiting their chemotaxis in response to CXCL12. PF-06747143 also induced cytotoxicity in AML cells via Fc-effector function. To characterize the effects of PF-06747143 on leukemia progression, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
(38 reference statements)
2
25
0
Order By: Relevance
“…In addition, two independent studies have recently targeted CXCR4 with an IgG antibody (PF-06747143), which revealed a strong affinity to AML cells and inhibited their chemotaxis towards CXCL12. It also reduced the tumor burden in other hematological malignancies and in a xenotransplantation model for AML Zhang et al, 2017).…”
Section: Targeting the Bmm In Hematological Malignanciesmentioning
confidence: 93%
“…In addition, two independent studies have recently targeted CXCR4 with an IgG antibody (PF-06747143), which revealed a strong affinity to AML cells and inhibited their chemotaxis towards CXCL12. It also reduced the tumor burden in other hematological malignancies and in a xenotransplantation model for AML Zhang et al, 2017).…”
Section: Targeting the Bmm In Hematological Malignanciesmentioning
confidence: 93%
“…LY2624587 is another anti-CXCR4 IgG4 antibody with similar mode of action, which has also reached the clinical trial phase (Table 2) (Peng et al, 2016b). The combination of CXCR4 inhibition, induction of apoptosis, and ADCC and CDC effector functions is employed in an IgG1 from Pfizer, PF-06747143, and shows a strong effect in multiple hematologic tumor models (Table 2) (Kashyap et al, 2017;Liu et al, 2017;Zhang et al, 2017). Utilization of different antibody formats and Fc engineering strategies provides an attractive flexibility in pursuing specific therapeutic needs.…”
Section: Targeting Cxcr4 and Ackr3 With Antibodiesmentioning
confidence: 99%
“…Similarly, CXCR4+ cancer cells are metastatic stem cells in several solid tumors [12][13][14][15][16][17]. Consequently, different groups are developing small drug CXCR4 inhibitors for AML therapy [5,7,18] aimed at eliminating CXCR4+ LSCs, responsible for AML aggressiveness and patient death.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%